Qualitative Research Courses in Higher Education: Limitations and Challenges - Aguilar, Jorge (CIEX JOURNAL, 2016)
Research courses do not seem to help students understand the fundamentals of research or develop skills in planning and conducting coherent qualitative inquiry. This talk will address the limitations and challenges of qualitative research courses offered in higher education institutions in Mexico, and it will discuss what it takes to design and to conduct reasonable qualitative research that leads to understanding what is happening in our schools and classrooms with a view to helping our language learners become more effective users of English.